REVIEW OF THE BOOK: STOP THE WORLD THAT I WANT TO UNDERSTAND. A GUIDE TO UNDERSTANDING THE CONFLICTS OUR TIMES (Journal of the Spanish Institute for Strategic Studies, 2018)
A bibliographic comment for this book writen by Antonio Navalón